An Analysis of Flouting Maxim in Ruby Spark Movie - Lasiana Lasiana Lasiana; Zia Hisni Mubarak (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This article describes the study of pragmatics in a specific domain of flouting maxim found in Ruby Spark movie. The aim of this study is to find out the type of flouting maxim found in the utterances between the characters in the movie. The theory used in this research was Grice (1972). In this research, the researcher applies the qualitative descriptive method. The method of collecting data is observation. The steps are watching the Ruby spark movie during their conversation. The result is there are four types of flouting maxims found in the movie. Eight data for flouting quantity, one for maxim of quality, and four for maxim of relevant and three for maxim of manner. And the most dominant flouting appear is maxim of quantity because they wanted to give additional information.